The Establishment and Kinds of Activities of Youth Sokil Society in Lviv at the End of XIX – at the Beginning of 20 Centuries - Папенко Є. (Видавничо-поліграфічний центр "Київський університет", 2015)
The article explores the activities of youth Sokil society in Lviv at the end of XIX – at the beginning of 20 centuries. Reasons for Sokil societies creation and an influence of Czech and Polish Sokils are analyzed. In the article it is discovered the influence of socio-political process, which happened on West Ukrainian lands at the end of XIX century, upon the birth and development of Sokil movement. It is mentioned of the role of "Vatra" and "Academic brotherhood" students' societies in Ukrainian Sokil creation. The main expansion ways of Sokil gymnastic and sport activity are determined. It is insisted that Ukrainian Sokil, being created ad exemplum of Czech and Polish ones, adopted only neighbors' names and organizational structure. It is mentioned of organizational structure of Ukrainian Sokil. Sport, gymnastic, fire-prevention, cultural and educational activity of Ukrainian Sokil Youth Society in Eastern Galicia at the end of XIX – at the beginning of XX centuries are explored. It is highlighted that Sokil educational system encouraged Ukrainians by its democracy, harmonious unification of immaterial and bodily parts, promoted national self-affirmation. Forms and methods of physical education are highlighted. The role and the meaning of the Lviv Sokil society in the widening network of the Sokil societies were enlightened in the article. It is underlined that V. Nahirnyi, V. Lavrivskyi, I. Boberskyi, being organizers of the Sokil movement, rank particularly in the improvement of society activities and in the creation of Sokil societies in the Eastern Galicia at the end of XIX – at the beginning of XX centuries.

Стаття присвячена діяльності львівського молодіжного товариства "Сокіл" наприкінці ХІХ – початку ХХ ст. Проаналізовані причини створення сокільських товариств та вплив чеського й польського сокільства. Розкрито вплив соціально-політичних процесів, які відбулись на західноукраїнських землях наприкінці XIX ст., на зародження та розвиток сокільства. Розглядається роль студентських товариств "Ватра" та "Академічне братство" у створенні українських "Соколів". Визначено основні шляхи поширення сокільського гімнастично-спортивного руху. Наголошується, що українські "Соколи" виникаючи за чеським та польським зразком, від сусідніх народів запозичили лише назву та організаційну структуру. Зазначається про структуру та організаційну будову українських "Соколів". Розкрито гімнастично-спортивну, протипожежну та культурно-просвітницьку діяльність українського молодіжного товариства "Сокіл" у Східній Галичині наприкінці ХІХ – початку ХХ ст. Підкреслено, що сокільська система виховання заохочувала українців своєю демократичністю, гармонійним поєднанням духовності й тілесності, сприяла національному самоутвердженню. Висвітлено форми та засоби фізичного виховання. Акцентується увага на значенні гімнастики та спорту для українського народу напередодні Першої світової війни. Висвітлено роль та значення львівського товариства "Сокіл" у розбудові мережі сокільських товариств. Підкреслено окреме місце В. Нагірного, В. Лаврівського, І. Боберського – організаторів українського сокільського руху в удосконаленні діяльності товариства та створенні сокільських осередків у Східній Галичині наприкінці ХІХ – початку ХХ ст.
Заснування та напрями діяльності молодіжного товариства "Сокіл" у Львові наприкінці ХІХ – початку ХХ ст.
Keywords: Eastern Galicia; Sokil movement; youth society; the national liberation struggle; government formation process; Східна Галичина; сокільський рух; молодіжні товариства; національно-визвольна боротьба; державотворчі процеси